Organ procurement coordinators’ experiences with family refusals in cadaveric organ donation: a qualitative analysis - Hi̇cran Karataş; Şener Balas (BMJ Open)
Objectives Organ procurement coordinators (OPCs) play a pivotal role in navigating end-of-life and second-birth narratives by securing familial consent for solid organ donation. Given the low rates of cadaveric organ donation in Türkiye and worldwide, OPCs are essential in advocating for and facilitating these donations. This study explores the reasons for refusal that OPCs have encountered during the familial consent process.Design We gathered the data through semistructured interviews with 30 OPCs. Thematic analysis was used to identify and analyse key themes, with a specific focus on cultural, religious, spiritual and folkloric barriers contributing to the low rates of cadaveric organ donation in Türkiye.Setting Hospitals and organ transplant centres operating under the jurisdiction of the Ankara Regional Coordination Centre in Türkiye.Participants Participants were recruited using a purposeful random sampling strategy to enhance credibility and reduce bias. Eligible informants included OPCs with at least 2 years of experience in the role. Among the 30 participants, 18 were based in central organ transplant centres associated with Training and Research Hospitals in Ankara, and 12 were from peripheral city hospitals.Results Coordinators identified five main barriers that hinder their ability to secure familial consent for cadaveric organ donation: (1) religion, (2) concerns about the wishes of the deceased, (3) desire to choose recipients, (4) familial dynamics and (5) folklore. Each category was further contextualised through subcategories derived from the frequency and nuances of recurring themes.Conclusion OPCs face significant challenges in promoting cadaveric organ donations due to cultural barriers. Their experiences underscore the need for culturally competent approaches in organ donation campaigns and the importance of supporting coordinators in their roles. Enhanced cultural understanding and targeted interventions could improve cadaveric organ donation rates.